Pseudepigrapha of the Old Testament as Part of Christian Literature : The Case of the Testaments of the Twelve Patriarchs and the Greek Life of Adam and Eve - Jonge, Marinus de (Brill Book Archive Part 1, ISBN: 9789004472495., 2003)
The primary witnesses of the writings called Pseudepigrapha of the Old Testament are, in great majority, of Christian provenance. It has been customary for scholars to look for an originally Jewish form of the documents, reflecting Jewish life and thought in the period between 200 BCE and 100 CE. In this volume, M. de Jonge argues that these writings should, first of all, be studied as documents relevant for Christians. This volume incorporates essays written earlier by the author as well as a number of new chapters. The first part deals with general questions concerning the transmission of the pseudepigrapha of the Old Testament whereas the second part has a particular focus on the Testaments of the Twelve Patriarchs and the Greek Life of Adam and Eve .